2006
DOI: 10.1017/s0265021506000354
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane preconditioning-induced cardio-protection in patients undergoing coronary artery bypass grafting

Abstract: The present results support the preconditioning effect of isoflurane in patients undergoing coronary artery bypass graft surgery as clinically feasible and providing optimal cardiac protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 36 publications
0
28
0
1
Order By: Relevance
“…Interfering effects of anesthetics such as isoflurane [38], opioids [39] and propofol [34] are frequently debated when it comes to assessing RIPC effects on serum cardiac markers, but a consensus onto what extent they interfere with RIPC has not been reached. RIPC has been demonstrated to reduce postoperative levels of circulating cardiac markers both with [34] and without isoflurane [1], while other studies found no such effect with [40] or without isoflurane [35], or with propofol [34].…”
Section: Discussionmentioning
confidence: 99%
“…Interfering effects of anesthetics such as isoflurane [38], opioids [39] and propofol [34] are frequently debated when it comes to assessing RIPC effects on serum cardiac markers, but a consensus onto what extent they interfere with RIPC has not been reached. RIPC has been demonstrated to reduce postoperative levels of circulating cardiac markers both with [34] and without isoflurane [1], while other studies found no such effect with [40] or without isoflurane [35], or with propofol [34].…”
Section: Discussionmentioning
confidence: 99%
“…133 Volatile anesthetics (sevoflurane, isoflurane, and desflurane) have, in several experimental and clinical settings, been shown to protect the heart from I/R injury. [134][135][136][137] Recently, isoflurane was demonstrated to have a similar effect on the rat liver, 138 and sevoflurane, in a prospective randomized study, protected the human liver from I/R injury during liver resection. 139 It is our practice to administer volatile anesthetics at least during the last 30 min before aortic cross clamping.…”
Section: Pulmonary Carementioning
confidence: 98%
“…39, 40 Its precise role in myocardial tissue remains to be resolved. It has been suggested that several anesthetic agents including isoflurane, 41 opioids, 42 and propofol 43 have preconditioning effects that may interfere with RIPC. However, results are inconsistent and reduced cardiac enzyme release after RIPC has been demonstrated in cardiac surgery both with 44 and without isoflurane.…”
Section: Circulation Research February 28 2014mentioning
confidence: 99%